Investigating the Factors Affecting the Performance of Businesses in Science and Technology Parks - Akbar Bahmani; Farshid Aslani; Seyyed Reza Mousavizadeh (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: This study aims to explain the factors affecting the performance of businesses located in the Science and Technology Park. Therefore, by understanding this issue through Interpretive-Structural Analysis (ISA), this research seeks to design a model based on the classification and segregation of factors affecting the performance of companies located in the Science and Technology Park.Methodology: The present research is applied in terms of purpose, descriptive nature, and survey in the data collection method. The research methodology is a qualitative-quantitative mix in the qualitative part based on identifying factors related to business performance. The work is located in the Science and Technology Park through interviews and content analysis with the participation of 15 experts as panel members, and in a small part through the formation of a structural self-interaction matrix seeks structural and interpretive modelling in which 15 senior managers and experts from science and technology parks participated.Findings: The results show that the most important factors affecting the performance of companies in the science and technology park are creativity, effectiveness, and work interactions, which were effective indicators in the thematic analysis results.Originality/Value: The most effective factors in the performance of companies located in the Science and Technology Park are the factors of job satisfaction, job freshness, and job trust and profession.